Development and preliminary evaluation of a diagnostic assay for neurosyphilis using a reverse transscription-polymerase chain reaction approach - Sindle, Jinny Charmaine (Division of Medical Microbiology, 2025)
Clinical diagnosis of neurosyphilis is difficult as it manifests non-specific symptoms which can be confused with other diseases. Laboratory diagnosis is also problematic, as an increase in mononuclear cell and protein concentrations in cerebrospinal fluid (CSF) is non-specific. A treponemal serological assay, using CSF, the CSF-fluorescent treponemal antibody-absorption (FTA-ABS) is very sensitive but has a low specificity for neurosyphilis. On the other hand, the CSF-Venereal Disease Research Laboratory (VDRL) has high specificity for neurosyphilis, but a low sensitivity. The aim of this project was to develop a sensitive and specific diagnostic assay for neurosyphilis to detect the etiological agent of syphilis, Treponema pallidum, using a reverse transcription-polymerase chain reaction (RT-PCR) approach. A critical component of this assay is the inclusion of a positive control that can be used on each sample. The size of the T. pa/lidum amplicon is 366 bp and that of the positive control is 950 bp. This positive control would allow for control of the RNA extraction process as well as the RT-PCR amplification. The positive control plasmid was constructed by ligating a 366 bp region, amplified from T. pallidum 16S rRNA gene, into a vector to form a phase I plasmid. PCR on the plasmid would yield a 366 bp amplicon. To distinguish between nucleic acids originating from T. pallidum and that of the positive control, spacer DNA was inserted into the phase I plasmid. PCR on the selected positive control plasmid yields a PCR amplicon of 950 bp. E. coli JM109 harbouring a positive control plasmid was used to spike CSF clinical samples. The sensitivity of the RT-PCR reaction using T. pallidum RNA was optimised and the assay could detect 101 T. pallidum equivalents of RNA The optimal quantity of the positive control was determined to be 5 x 10 3 E. coli positive control cells, and 15 μI of eluted RNA was used in the RT-PCR reactions. A small pilot study was performed to evaluate the RT-PCR assay, using 30 CSF samples from selected patients at the Department of Ophthalmology, Groote Schuur Hospital, Cape Town. Routine laboratory tests for neurosyphilis were performed on the CSF samples, and left over CSF was used for the RT-PCR assay. There were no false positive RT-PCR results in the 'syphilis and neurosyphilis excluded' categories. The RT-PCR assay yielded a true positive result for a definite neurosyphilis patient. In addition, the RT-PCR assay yielded one positive result out of 8 'possible neurosyphili,s' cases. It is not clear whether this patient had secondary syphilis (with central nervous system invasion by T. pal/idum) or neurosyphilis; however as with all laboratory tests, clinical correlation should be performed. The RT-PCR negative results of the seven other 'possible neurosyphilis' patients were difficult to evaluate. It is possible that RT-PCR assay missed three samples positive for T. pallidum as they had features suggestive of neurosyphilis. In future, cells from CSF will be stored in an RNA stabilisation reagent, and 5, 10 and 15 μI RNA eluate will be used in the RT-PCR reaction, which may increase sensitivity of the assay. This RT-PCR assay shows promise as a routine diagnostic assay, and may facilitate laboratory diagnosis of neurosyphilis. However, a more in-depth evaluation of the RT-PCR assay must still be performed.